2D-QSAR, Docking Studies, and In Silico ADMET Prediction of Polyphenolic Acetates as Substrates for Protein Acetyltransferase Function of Glutamine Synthetase of Mycobacterium tuberculosis. (17th February 2013) - Ponnan, Prija; Gupta, Shikhar; Chopra, Madhu; Tandon, Rashmi; Baghel, Anil S.; Gupta, Garima; Prasad, Ashok K.; Rastogi, Ramesh C.; Bose, Mridula; Raj, Hanumantharao G.
Abstract : A novel transacetylase (TAase) function of glutamine synthetase (GS) in bacterial species such as Mycobacterium smegmatis and Mycobacterium tuberculosis H37Rv was established by us, termed as mycobacterial TAase (MTAase). Several polyphenolic acetates (PAs) were found to be substrates for MTAase by inhibiting certain receptor proteins such as glutathione S-transferase by way of acetylation. The present work describes the descriptor-based 2D-QSAR studies developed for a series of PA synthesized by us and evaluated for MTAase and antimycobacterial activity using stepwise multiple linear regression method with the kinetic constants and the minimum inhibitory constant (MIC) as the dependent variables, to address the fact that TAase activity was leading to the antimycobacterial activity. Further, blind docking methods using AutoDock were carried out to study the interaction of potent PA with the crystal structure of M. tuberculosis GS. PAs were predicted to bind M. tuberculosis GS on the protein surface away from the known active site of GS. Subsequent focussed/refined docking of potent PA with GS showed that theε -amino group of Lys4 of GS formed a cation-π interaction with the benzene ring of PA. Also, ADMET-related descriptors were calculated to predict the pharmacokinetic properties for the selection of the effective and bioavailable compounds.